Metabolic syndrome is associated with exposure to organochlorine pesticides in Anniston, AL, United States. (November 2017) - Rosenbaum, Paula F.; Weinstock, Ruth S.; Silverstone, Allen E.; Sjödin, Andreas; Pavuk, Marian
Abstract: The Anniston Community Health Survey, a cross-sectional study, was undertaken in 2005–2007 to study environmental exposure to polychlorinated biphenyl (PCB) and organochlorine (OC) pesticides and health outcomes among residents of Anniston, AL, United States. The examination of potential risks between these pollutants and metabolic syndrome, a cluster of cardiovascular risk factors (i.e., hypertension, central obesity, dyslipidemia and dysglycemia) was the focus of this analysis. Participants were 548 adults who completed the survey and a clinic visit, were free of diabetes, and had a serum sample for clinical laboratory parameters as well as PCB and OC pesticide concentrations. Associations between summed concentrations of 35 PCB congeners and 9 individual pesticides and metabolic syndrome were examined using generalized linear modeling and logistic regression; odds ratios (OR) and 95% confidence intervals (CI) are reported. Pollutants were evaluated as quintiles and as log transformations of continuous serum concentrations. Participants were mostly female (68%) with a mean age (SD) of 53.6 (16.2) years. The racial distribution was 56% white and 44% African American; 49% met the criteria for metabolic syndrome. In unadjusted logistic regression, statistically significant and positive associations across the majority of quintiles were noted for seven individually modeled pesticides ( p, p ′-DDT, p, p ′-DDE, HCB, β -HCCH, oxychlor, tNONA, Mirex). Following adjustment for covariables (i.e., age, sex, race, education, marital status, current smoking, alcohol consumption, positive family history of diabetes or cardiovascular disease, liver disease, BMI), significant elevations in risk were noted for p, p ′-DDT across multiple quintiles (range of ORs 1.61 to 2.36), for tNONA (range of ORs 1.62–2.80) and for p, p ′-DDE [OR (95% CI)] of 2.73 (1.09–6.88) in the highest quintile relative to the first. Significant trends were observed in adjusted logistic models for log10 HCB [OR = 6.15 (1.66–22.88)], log10 oxychlor [OR = 2.09 (1.07–4.07)] and log10 tNONA [3.19 (1.45–7.00)]. Summed PCB concentrations were significantly and positively associated with metabolic syndrome only in unadjusted models; adjustment resulted in attenuation of the ORs in both the quintile and log-transformed models. In conclusion, several OC pesticides were found to have significant associations with metabolic syndrome in the Anniston study population while no association was observed for PCBs. Highlights: Metabolic syndrome was highly prevalent in a cohort of Anniston, AL residents, USA. The role of organochlorine pollutants in metabolic syndrome was examined. The sum of 35 polychlorinated biphenyls was not associated with metabolic syndrome. Positive associations noted for some organochlorine pesticides and metabolic syndrome. Modeled results, with and without total lipids are presented and discussed.